Association between vitamin D deficiency and diabetic foot ulcer wound in diabetic subjects: A meta‐analysis. Issue 1 (14th May 2022) - Lin, Juan; Mo, Xinxin; Yang, Yejun; Tang, Chao; Chen, Jia
Abstract: A meta‐analysis was performed to evaluate the association between vitamin D deficiency and diabetic foot ulcer wounds in diabetic subjects. A systematic literature search up to March 2022 incorporated 7586 subjects with diabetes mellitus at the beginning of the study; 1565 were using diabetic subjects with foot ulcer wounds, and 6021 were non‐ulcerated diabetic subjects. Statistical tools like the dichotomous and contentious method were used within a random or fixed‐influence model to establish the odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) to evaluate the influence of vitamin D deficiency in managing diabetic foot ulcer wound. Diabetic subjects with foot ulcer wounds had significantly lower vitamin D levels (MD, −6.48; 95% CI, −10.84 to −2.11, P < .004), higher prevalence of vitamin D deficiency (<50 nmoL/L) (OR, 1.82; 95% CI, 1.32‐2.52, P < .001), and higher prevalence of severe vitamin D deficiency (OR, 2.53; 95% CI, 1.65‐3.89, P < .001) compared with non‐ulcerated diabetic subjects. Diabetic subjects with foot ulcer wounds had significantly lower vitamin D levels, higher prevalence of vitamin D deficiency, and higher prevalence of severe vitamin D deficiency compared with non‐ulcerated diabetic subjects. Further studies are required to validate these findings.